2009
DOI: 10.1002/mnfr.200800302
|View full text |Cite
|
Sign up to set email alerts
|

Selective bio‐availability of phenolic acids from Scottish strawberries

Abstract: Scottish strawberries were found to be a rich source of phenolic acids, namely benzoic (1287.95 +/- 279.98 mg/kg) and cinnamic (1159.40 +/- 233.96 mg/kg) acids, both free and attached to other plant components. Studies suggest a chemopreventive role for such compounds in several major clinical conditions, but the anticipated benefits are likely to be affected by their bio-availability and metabolic fate. In this pilot study, strawberries (750 g) was consumed by four healthy human volunteers (32 +/- 6 years). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 29 publications
5
42
0
1
Order By: Relevance
“…The magnitudes of apparent binding constants for g-globulin were almost in the range of 10 3 -10 5 L/mol, which were similar to recent report for g-globulin by He et al [12]. However, these data were much smaller than the affinities of polyphenols for BSA and HSA from our previous reports (10 4 -10 8 /M) [14][15][16][17].…”
Section: The Binding Constants (K a ) And The Number Of Binding Sitessupporting
confidence: 88%
“…The magnitudes of apparent binding constants for g-globulin were almost in the range of 10 3 -10 5 L/mol, which were similar to recent report for g-globulin by He et al [12]. However, these data were much smaller than the affinities of polyphenols for BSA and HSA from our previous reports (10 4 -10 8 /M) [14][15][16][17].…”
Section: The Binding Constants (K a ) And The Number Of Binding Sitessupporting
confidence: 88%
“…11 Moreover, some studies have shown that the concentration of 4-hydroxybenzoic acid increased in plasma and urine aer strawberry consumption by healthy volunteers 32 and in the urine of rats fed with wine powder. 33 Syringic acid may come from malvidin degradation described from Lactobacillus and Bidobacterium.…”
mentioning
confidence: 99%
“…Of the secondary metabolites, the group most widely studied are products of the phenylpropanoid pathway, as nearly all plant foods considered to have cancerpreventative properties are rich in these compounds (73) including cinnamic, phenylacetic, phenylpropionic, coumarins, flavonoids and anthocyanidins (72) . Although these phenylpropanoid derivatives are most widely studied, many other secondary metabolites and their derivatives are present in the human colon.…”
Section: Phytochemicalsmentioning
confidence: 99%